Study of Stark broadening of krypton helium-β lines and estimation of electron density and temperature in NIF compressed capsules. (1st October 2022) - Hill, K W; Gao, L; Kraus, B F; Bitter, M; Efthimion, P C; Pablant, N; Schneider, M B; Thorn, D B; Chen, H; Kauffman, R L; Liedahl, D A; MacDonald, M J; et al.
Abstract: The National Ignition Facility (NIF) diagnostic instrument manipulator (DIM) - based high resolution (dHIRES) x-ray spectrometer was used to measure the time evolution of the electron density ( n e ) and temperature ( T e ) in the hot spot of four NIF compressed capsules with 25 ps time resolution during the 'stagnation' phase. The electron density was inferred by comparing the measured Stark broadening of the krypton (Kr) He β spectral complex with theoretical calculations that include ion dynamic effects, and the electron temperature was inferred by comparing the measured ratio of the intensity of a dielectronically excited Li-like Kr line to the intensity of the Kr He β resonance line with calculations using the spectroscopic collisional radiative atomic model (SCRAM) and CRETIN collisional-radiative models. The inferred, time averaged n e values mainly agree with n e values from neutron diagnostics within uncertainties, but the neutron time-of-flight values of T ion are consistently higher than dHIRES T e values by 200–700 eV. The dHIRES measurements and measurement techniques, method of uncertainty analysis, and discussion of comparisons with measurements from neutron diagnostics are presented.